Research Progress of TiN Formation and Control in the Smelting Process of Ti-Microalloyed Steel - Yang Rui, Li Yang, Sun Meng, Ma Shuai, Mao Yunqie, Jiang Zhouhua (Teshugang)
Titanium-microalloyed steel is widely used in aerospace， automotive manufacturing， construction engineering and other fields. Adding Ti to the steel for microalloying can obviously increase the strength and improve the properties of the material， but TiN inclusions will be formed in the steel. The precipitation temperature of TiN is high， fine TiN inclusion can inhibit the growth of grain at high temperature， and induce the formation of inocrystalline needle ferrite （IAF）；And the thick TiN inclusion is unfavorable to the properties of the material. In this paper， the latest progress in the formation of TiN in Ti-bearing microalloyed steels at home and abroad is discussed from two aspects of the formation and control of TiN. On the formation of TiN， this paper mainly summarizes the influence TiN of formation mode ，morphology characteristics， thermodynamic and kinetic factors on the formation of TiN， as well as the harm of TiN in steel on the properties of steel. On the control of TiN， the effects of the synergistic action of Al， B and Ti on the formation of TiN， the effects of Mg treatment， Ca treatment， and rare earth （Ce， La， Y） treatment on the formation of TiN in steel are mainly summarized in this paper.The amount， size and morphology of TiN can be affected by the synergistic effect between other elements and Ti element in steel. Mg treatment， Ca treatment and rare earth treatment can provide effective nucleation inclusion for the formation of TiN， while reducing the formation of large size TiN inclusion. After Mg， Ca and rare earth treatment， TiN composite inclusions of sub-micron and nano-scale can be formed， which can effectively induce the formation of IAF and strengthen the properties of steel.